Dinamika Kebijakan Pangan Orde Baru: Otonomi Negara vs Pasar Global - Fatih Gama Abisono (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2002)
Food policy is not independently designed, as it is structurally hound. State's autonomy is even more questionable as globalized-politicaleconomic structure gaining stronger grip in Indonesia, especially after monetary crisis at the end of New Order period.